Brief report: Overgeneral autobiographical memory in adolescent major depressive disorder. (4th August 2016) - Champagne, Katelynn; Burkhouse, Katie L.; Woody, Mary L.; Feurer, Cope; Sosoo, Effua; Gibb, Brandon E.
ABSTRACT: The current study examined whether overgeneral autobiographical memory (OGM) bias serves as a state‐like marker of major depressive disorder (MDD) in adolescence or whether it would also be observed in currently nondepressed adolescents with a history of MDD. We examined differences in OGM to positive and negative cue words between adolescents (aged 11–18 years) with current MDD ( n  = 15), remitted MDD ( n  = 25), and no history of any depressive disorder ( n  = 25). Youth and their parents were administered a structured diagnostic interview and adolescents completed the autobiographical memory test. Compared to never depressed adolescents, adolescents with current or remitted MDD recalled less specific memories in response to positive and negative cue words. The difference between the two MDD groups was small and nonsignificant. These findings suggest that OGM is not simply a state‐like marker in currently depressed adolescents, but is also evident in adolescents with remitted MDD, indicating that it may represent a trait‐like vulnerability that increases risk for relapse.